Descriptive Study : Overview of Clean and Healthy Living Behavior (PHBS) at COVID-19 Survivors in X Sub-district, Surakarta City, Indonesia - Syarifah (International Journal of Seocology, 2020)
Clean and Healthy Living Behavior (PHBS) is a group of behaviors carried out on the basis of self-awareness as a result of learning, which makes a person, family, group or community able to help themselves (independently) in daily life, especially in the field of health and play an active role in realizing public health. WHO has established a special unit and ordered the whole world to adhere to the rules and stages in order to accelerate healing around the world. Even from WHO has emphasized all the time to do a clean lifestyle or what in Indonesia is called PHBS, among others physical distancing, wearing masks, keeping rooms well ventilated, avoiding crowds, cleaning hands, and when coughing closes with elbows (WHO, 2021b). Therefore, researchers are interested to know the overview of clean and healthy living behavior (PHBS) in COVID-19 survivors in X Sub-district Surakarta City, Indonesia. This research was conducted in December 2021 in sub-district X in Surakarta City, Indonesia. Covid19 survivor data in Surakarta city in December as many as 5340 people and in sub-district x as many as 412 people recovered from COVID19. For this study, a sample of 52 reponden was obtained. The characteristics of the respondents observed by the researchers were gender, age, occupation, marital status. A total of 52 respondents were taken randomly in sub-district X, Surakarta City obtained results that spread evenly. The results showed that the characteristics of respondents as COVID19 Survivors were known that the even distribution in the female sex was 53.8%, seen in terms of age in the age range under 20 years of age of 28.8%, dominated by people working in the private sector by 50.0% with married status of 65.4%. COVID19 Survivor behavior patterns include exercise behavior, hand washing habits, mask-wearing behavior and outdoor activity patterns.